Inhalation of Bacterial Cellulose Nanofibrils triggers an inflammatory response and changes lung tissue morphology of mice - Silva-Carvalho, R (2019)
In view of the growing industrial use of Bacterial cellulose (BC), and taking into account that it might become airborne and be inhaled after industrial processing, assessing its potential pulmonary toxic effects assumes high relevance. In this work, the murine model was used to assess the effects of exposure to respirable BC nanofibrils (nBC), obtained by disintegration of BC produced by Komagataeibacter hansenii. Murine bone marrow-derived macrophages (BMMF) were treated with different doses of nBC (0.02 and 0.2 mg/mL, respectively 1 and 10 µg of fibrils) in absence or presence of 0.2% Carboxymethyl Cellulose (nBCMC). Furthermore, mice were instilled intratracheally with nBC or nBCMC at different concentrations and at different time-points and analyzed up to 6 months after treatments. Microcrystaline Avicel-plus® CM 2159, a plant-derived cellulose, was used for comparison. Markers of cellular damage (lactate dehydrogenase release and total protein) and oxidative stress (hydrogen peroxidase, reduced glutathione, lipid peroxidation and glutathione peroxidase activity) as well presence of inflammatory cells were evaluated in brochoalveolar lavage (BAL) fluids. Histological analysis of lungs, heart and liver tissues was also performed. BAL analysis showed that exposure to nBCMC or CMC did not induce major alterations in the assessed markers of cell damage, oxidative stress or inflammatory cell numbers in BAL fluid over time, even following cumulative treatments. Avicel-plus® CM 2159 significantly increased LDH release, detected 3 months after 4 weekly administrations. However, histological results revealed a chronic inflammatory response and tissue alterations, being hypertrophy of pulmonary arteries (observed 3 months after nBCMC treatment) of particular concern. These histological alterations remained after 6 months in animals treated with nBC, possibly due to foreign body reaction and the organism's inability to remove the fibers. Overall, despite being a safe and biocompatible biomaterial, BC-derived nanofibrils inhalation may lead to lung pathology and pose significant health risks.